Hiding data in video file: an overview - Al-Frajat, A.K.; Jalab, H.A.; Kasirun, Z.M.; Zaidan, A.A.; Zaidan, B.B. (Asian Network for Scientific Information (ANSINET), 2010)
The aim of this review is to study the methods of steganography using the video file as a cover carrier. The steganography is the art of protecting the information through embedding data in medium carrier, for instants this study illustrate historically this art, as well as the study describes methods as a review for this art in the video file. The video based steganography can be used as one video file, separated images in frames or images and audio files. Since that, the use of the video based steganography can be more eligible than other multimedia files. As a result of this study, the video based steganography has been discussed and the advantages of using the video file as a cover carrier for steganography have been proposed.